A Survey on Biosecurity and Animal Welfare in Twenty-Five Beef Cattle Farms in the Marche Region, Central Italy: Application of the ClassyFarm Checklists - Filippo Alquati; Martina Quagliardi; Alessandra Gavazza; Alessandra Roncarati; Livio Galosi; Corrado M. Corradini (Animals)
In Italy, the livestock sector is facing a crucial transformation phase towards a production system able to guarantee a high standard of health and animal welfare. With this aim, the ClassyFarm platform (CFp) has been activated by the Italian Ministry of Health, with a prominent role for farm veterinarians, who are responsible for the livestock farms’ evaluation and the entering of data for self-monitoring purposes into the information system. This work aimed to analyse the application of CFp in the biosecurity and animal welfare areas in twenty-five beef cattle farms of the Marche Region, Central Italy, using the checklists provided by the platform itself. The results, expressed in percentages, were compared with the national averages. The percentages of the animal welfare assessment, which were higher than the national average, are likely the result of improved management and a broad understanding of these indicators based on animal observations. At the same time, the biosecurity area, in line with the national average, resulted in much lower percentages, leading to the assessment that some farming areas should definitely be improved. This result reflects the non-intensive and family-run breeding type of breeding typical of this region, characterised by particular attention to animal welfare.